ANÁLISIS TRIBUTARIO DE LAS COMISIONES POR SERVICIOS DE LOS AGENTES INTERMEDIARIOS TEXTILES - López Siu, Tania Belky (2017)
The present evaluation allows to show that the commissions for the services of the textile intermediary agents, representatives of foreign companies, are unaffected by the general sales tax. Based on this objective, a descriptive analysis was carried out taking into account the variables of the research, obtaining as results, that the income from commissions when taxing with the general sales tax, represents a decrease of 15.26% in its economic performance , when the invoice is issued to the non-domiciled (final consumer), the textile intermediary assumes the tax by reducing the economic benefit of the operation. Due to the lack of inclusion in the tax norm of the general tax on sales of appendix v export of services, this type of activity generates controversies of normative interpretation, damaging the operational stability of the companies intermediate textile agents and the existence of confectionary companies exporters.